Needlescopic surgery for large umbilical hernia in a patient with morbid obesity using intraperitoneal onlay mesh with fascial defect closure: a case report - Hisataka Fujiwara; Takayuki Suto; Akira Umemura; Yota Tanahashi; Satoshi Amano; Kenichiro Ikeda; Kazuho Harada; Akira Sasaki (Surgical Case Reports)
Abstract Background The European and American guidelines recommend that symptomatic umbilical hernias (UHs) are repaired using an open approach with a preperitoneal flat mesh. However, the standard treatment procedure for large UH in patients with extreme obesity is yet to be established. Here, we present the first case of a patient with morbid obesity undergoing laparoscopic UH repair using needlescopic instruments and an intraperitoneal onlay mesh plus repair (IPOM plus). Case presentation A 29-year-old man, who was classified as morbidly obese (body mass index, 36.7 kg/m2) noticed a reducible nontender mass in the umbilical region and was subsequently diagnosed with an UH, with a diameter of 4 cm. Laparoscopic IPOM plus repair was planned using a needlescopic method for a large UH in the patient with morbid obesity. A 3-mm rigid laparoscope was mainly used in the procedure. After a 12-mm trocar and two 3-mm trocars were inserted, fascial defect closure was performed using intracorporeal suturing with 0 monofilament polypropylene threads. Then, IPOM was performed laparoscopically using an 11.4-cm round mesh coated with collagen to prevent adhesions. The operative time and blood loss were 57 min and 1 g, respectively. The postoperative course was uneventful. Conclusions Reduced-port laparoscopic surgery using needlescopic instruments and an IPOM plus technique is a minimally invasive and convenient combination option for large UH in a patient with morbid obesity.